Pattern of Type-II Anti-Diabetes Mellitus Drug Use in Inpatients in Regional General Hospital of NTB Province in 2023 - Adinda, Putri; Hasina, Raisya; Aini, Siti Rahmatul (Jurnal Biologi Tropis, 2025)
Diabetes Mellitus is a disease with the fifth highest mortality rate in the world because it can cause serious complications such as neuropathy, nephropathy, and retinopathy. This study aims to determine the pattern of use of antidiabetic type 2 drugs in hospitalized patients at the NTB Provincial Hospital in 2023. This study was retrospective using the Probability Sampling method, namely the Simple Random Sampling type, so that a sample of 90 medical records of patients with type 2 diabetes mellitus was obtained. The data were analyzed using chi-square test using Microsoft Excel and SPSS version 25. The results of the study showed that the use of insulin antidiabetic drugs with a fast-acting insulin class was the most prescribed antidiabetic drug with a total of 603 (42.33%), while oral antidiabetic drugs with a biguanide class, namely metformin, were the most widely used oral antidiabetic drugs with a total of 246 (52.45%). Gender, age, and BMI did not significantly correlate with patient blood sugar management, according to the Chi-Square test analysis (p value > 0.05). However, the blood sugar control treatment time revealed a p value < 0.05, indicating a substantial correlation between the two variables. The study concludes that, according to the pattern of type 2 antidiabetic medication usage among hospitalized patients at the NTB Provincial Hospital in 2023, the most commonly used medications in the NTB Provincial General Hospital during that year were 603 (42.33%) insulin class antidiabetic medications, specifically rapid-acting insulin.